Employment of Disabled Persons in Sheltered and Unsheltered Conditions During the COVID 19 Pandemic in Poland - Andrzej KOZA; Adriana POLITAJ (Communications of International Proceedings, 2022)
The aim of the article is an attempt to analyse the changes taking place in the sheltered and open labour market in Poland and other countries during the COVID 19 pandemic. Disabled people are commonly considered to be at risk of social exclusion under standard conditions of the world economy. The crisis caused by the pandemic may have exacerbated this risk. Therefore, the authors decided to look at the impact of COVID-19 pandemic on the employment of disabled people and consequently to examine the efficiency of governmental initiatives aimed at protecting jobs and employers functioning in the sheltered and unsheltered environments respectively. The motivation to undertake research in this area was the willingness to continue our long-term research into the labour market situation of people with disabilities, and to enrich the knowledge on the evolution of this market. The period of the COVID -19 pandemic seems a favourable moment to verify the efficiency of labour market protection instruments in the situation of major socio-economic changes. In the past, such conditions frequently caused the market-driven mechanisms to disappoint (e.g. during the crisis of 2007-2008). The article presents a descriptive and comparative analysis based on research involving both the world's leading literature and the statistical data available on the subject. The time frame of the research covered the years 2019-2020 as well as the five initial months of 2021, thanks to the availability of consistent statistical data.
Keywords: COVID -19 pandemic; disability; sheltered labour market; open labour market.